POTENSI SUMBERDAYA PERIKANAN DAN PENGELOLAANNYA UNTUK MENDUKUNG KEHIDUPAN SOSIAL EKONOMI MASYARAKAT DI RAWA DANAU BANGKAU - Emmy Sri Mahreda; Tri Dekayanti (Universitas Lambung Mangkurat, 2012)
The goals if this research are : 1) Knowing the potencial of the fish catching source include the kind of fish, tha medium and the infractructure, the capital source, the oca public role, and the properness of the fish fish catching business. 2) Knowing the potentials of the fishery source include the kind of fish which are cultured, the medium and the infrastructure of the fish culture, the capital source, the fish culture technique, and the properness of this fish culture. 3) knowing the potentials of the fish processing source, the kind of processing, the medium and infrastructure, the capital source, the technique of processing, and the properness of the fish processing business . 4) knowing the village economy institute, the marketing channel. 5) Analizing the fishery source management in Rawa Bangkau. The method used in research are the descriptive and the purposhing method, while the responden determination is done by the random sampling. The people approach is done by using the snowball method. The demography parameter, the social culture and the idenfication of the various fish culture source will be analized descriptively . The Investment criterion by using Net Present Value (NPV), the Internal Rate of Return (IRR) and the Benfit Cost Ratio (BCR) approach are used to know the properness of the fishery business. The analysis method used for the marketing system is the sample linier regression, while the S-C-P analysis is use to analyze the market structure, the market conduct and the market performance include the price share and the marketing margin, the marketing channel is analyzed by using the descriptive analysis. Keyword : Danau Bangkau, participatory Rural Appraisal fied study, Invesment Criterion, S-C-P analysis. The results of this research are : 1) the fish catching business in Rawa Bangkau is potential enough the production 3.428,4 tons in 2011. This business is poper to be develoved because the NVP 10 % > 0, the Gross BCR > 1, and the IRR > the intersest rate in the bank. 2) the fish cuture develoved in Rawa Bangkau are the well-fish culture and the cges-fish cuture. Both of them are prper to be develoved financially based on the NVP, the Net BCR, and the IRR. 3) The fish processing business done by the people in Rawa Bangkau is the makin of dried-salty fish. The kinds of fish processed are sepat rawa, sepat siam, gabus, betok, and biawan. This business is Gros BCR, and the IRR. 4) The marketing of the fish processing product is still decided by the collector, while the fish catcheris only as the price receiver. Based on the conduct structure and the market performance, it tends to be imferpect competition market (oligopsony/oligopoly). The marketing margin and the highest profit are gained by haruan product because the price and the demand of this fish are higher than other fish. The price share of the fish catcher is good enough, so that the catching business can be continued because there is the fish devesifikation to increase the family income. 5) The fishery management develoved in Rawa Bangkau is based on the local policy they have in order not to destry the fihesry source and its environment. The local policies are the prohibition of using the fishing gear that destroy the fishing source and the prohibition of catching the fish redundantly.